Ethnicity affects the risk factors of acute myocardial infarction and should be considered in educational programs - Alharbe, Umar Abdolah; Alatawi, Hanad Hassan; Amirthalingam, Palanisamy; Daghriri, Sultan Mohammed; Alhwiti, Alanoud Abduallah; Alenazi, Tahani Saud; Al Ahmare, Abdulelah Turki S.; Zaitone, Sawsan A.; Aljabri, Ahmed; Hamdan, Ahmed Mohsen (Frontiers in Cardiovascular Medicine, 2022)
Acute Myocardial infarction is a non-communicable disease representing the leading cause of death in Saudi Arabia. Studying the ethnicity in its risk factors has been poorly investigated. Objectives To compare risk factors among Saudi nationals and expatriates. Methods A retrospective cohort study for patients admitted to the Cardiac Care Unit of one of the largest tertiary care hospitals in Tabuk diagnosed with acute myocardial infarction from September 2018 to August 2019. Risk factors were compared among groups on the basis of their ethnicity. Results In total 18,746 patients were included. Gender and age were the predominant risk factors; Male (p < 0.05) and age >50 years (p < 0.05). There were significant differences between Saudis and expatriates in all measurable parameters indicating that a genetic factor contributes to the risk factors, which was proved by the significant differences between the Middle East North Africa and South Asia subgroups. Interestingly, the mean values of laboratory results were higher than Saudi populations. Conclusions The disparity in lipid profile among the studied groups addresses the patient ethnicity should be considered during education programs for the risk factors of cardiovascular disease.